Supporting Entrepreneurship from Public Funds during the Major Economic Disruptions: Polish Evidence - Justyna ZYGMUNT (Communications of International Proceedings, 2020)
This paper uses a data set for the Polish economy covering the early months of the COVID-19 pandemic (March-August 2020) to examine how the economic downturn has been responded in Poland through establishing “first aid” supporting programs to entrepreneurship. The focus is on the usage of funds that have been granted to Poland within the EU financial framework 2014-2020, and which have been re-directed to answer the urgent needs of enterprises. In particular, this paper addresses the following questions: (i) what were the phases of supporting entrepreneurship in Poland during the COVID-19 economic disruption from funds within EU financial framework 2014-2020, and (ii) what was the nature of that support? The study makes a contribution to the entrepreneurship literature by providing a useful evidence of the approach towards supporting entrepreneurship during a major economic downturn. In particular, this paper finds that policy actions in Poland to support entrepreneurship from the EU funds within financial framework 2014-2020 have been two-tier, with the nationwide tier more likely to support medium enterprises and the regional tier focused primarily on supporting micro and small enterprises. It has been also observed that although the policy actions to respond to the COVID-19 effect on enterprises have been considerable, they remain relatively undifferentiated in terms of sectors and the regional specificity.
Keywords: Entrepreneurship; Economic Disruptions; Public Support; COVID-19; European Union; Poland